(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Ebstein’s anomaly is a rare malformation of the tricuspid valve, accounting for <1% of congenital heart disease. Despite its low incidence, it can have significant clinical ramifications as it encompasses anomalies of the tricuspid valve apparatus, the right ventricle, and the conduction system. Depending on the severity of these anomalies, clinical presentation can vary across a spectrum from no symptoms to critical illness at birth. Mortality remains relatively high, especially in prenatally diagnosed severe cases. The anomaly is complicated by its association with chromosomal disorders and extracardiac defects, seen in about 20% of cases.